2013
DOI: 10.1179/1743288x12y.0000000058
|View full text |Cite
|
Sign up to set email alerts
|

Supraspinal structures may be associated with hypoalgesia following thrust manipulation to the spine: a review of the literature

Abstract: Background: Thrust manipulation to the spine has been shown to be an effective treatment for pain reduction associated with musculoskeletal disorders. However, the mechanisms of action tied to this intervention have yet to be sufficiently explained.Objectives: This manuscript reviews the literature related to supraspinal mechanisms associated with pain inhibition, which may also be associated with hypoalgesia following spinal manipulation. Such information adds to the current body of evidence that has demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…In concert with these inhibitory afferent mechanisms or independently, descending pain inhibitory systems [ 77 , 78 ] also may be involved. Clinical research using functional magnetic resonance imaging in asymptomatic individuals has demonstrated that decreased remote peripheral pain rating immediately following spinal manipulative therapy was significantly related to reduced neuronal activation in brain regions associated with pain [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…In concert with these inhibitory afferent mechanisms or independently, descending pain inhibitory systems [ 77 , 78 ] also may be involved. Clinical research using functional magnetic resonance imaging in asymptomatic individuals has demonstrated that decreased remote peripheral pain rating immediately following spinal manipulative therapy was significantly related to reduced neuronal activation in brain regions associated with pain [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human imaging studies have begun to investigate brain correlates of a counterirritation phenomenon thought to be associated with manual therapy intervention. 32,33 For example, a counterirritation stimulus consisting of immersing the left contralateral foot in cold water decreased pain-related activation of several brain areas including the thalamus, primary somatosensory cortices, anterior cingulate cortex, and posterior insular cortex evoked by phasic electrical stimulation of the sural nerve in healthy volunteers. 61 Functional magnetic resonance imaging was used in a recent case series study to determine supraspinal activation in response to noxious mechanical stimuli applied before and after spinal manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Manipulation has been postulated to have hypoalgesic effects on local and distant areas of pain, 61 and we have examined the global hypoalgesic effects of thoracic manipulation. The reasons for the use of thoracic spine manipulation with noxious mechanical stimulation to the index finger, as opposed to cervical spine manipulation, are 2-fold: first, it is not possible to manipulate the cervical spine without imparting some head-neck motion in the x, y, and z directions (in/ out and along the main magnetic field).…”
Section: Limitationsmentioning
confidence: 99%